Influência das políticas de gestão de pessoas na constituição de comunidades de prática pela perspectiva da aprendizagem situada: evidências empíricas dos gestores de pequenas empresas familiares brasileiras - Goettems, Talita Bernardi (2019)
The theme of this dissertation is the learning process in the management of small family businesses for the constitution of communities of practice, permeated by the debate on the influence of two different people management policies (“prevention, health and labor safety”; “communication, transparency and dialogue”). The aim was to understand the possible influences of people management policies in the constitution of the communities of practice in small family businesses, located in the Northern region of Rio Grande do Sul state, managed by the owner family members. The theoretical assumption is that people management policies are formulated informally in small family businesses and that this is a contributing factor for the learning process and for the constitution of communities of practice. The located learning is a theoretical perspective of the organizational learning in which learning happens due to the situation, that undergoes context and cultural influences in which it occurs or is located, as well as the social interaction moment amongst the learners. It is argued that small family businesses trigger off the communities of practice because of the specificities of how they design and implement two of their people management policies. These policies are understood as a set of principles that guide the conduct of the members of the owner family and other workers in the general course of their practices. Such policies define the organization's positioning, expectations and values in the treatment given to people. It is also argued that there is a prevalence of people management policies developed from the strategical perspective on human resources, which represents a theoretical challenge regarding the theoretical perspective of located learning and the configuration of a way to study policies of people management in small family businesses in the Brazilian sociocultural content. This is an applied social research developed in the descriptive level, oriented by the multiple case study strategy, with a qualitative approach, whose scientificity is proven theoretically. The method used was the content analysis and the techniques applied were the categorical analysis, the structural analysis and the enunciation analysis. The perspective of the analysis is interpretative and takes place under the theoretical foundations of located learning, of people management, small businesses management and the specificities of a family business. This study resulted in the finding that, in Brazilian small family businesses, the member's interaction of two or more generations of the owner family, of relatives and of workers assimilated to members of the owner family triggers the formation of a type of communities of practice that belong to the “owner family”. People management policies are different for those who aren't members of the homeowner family when compared to the non-family members. Evidence was obtained by analyzing the different stages of development of small family businesses, in a historical-temporal perspective and in harmony with the dynamics of the owner family and the identification of elements that form the people management policies and the learning process which triggers communities of practice. It is concluded that people management policies in small family businesses influence the constitution of communities of practice among the members of the owner family, and communities of practice constituted only by non-family members were not identified.